Penyelenggaraan Operasional Pemesanan, Penerimaan, Penyimpanan, dan Pendistribusian Bahan Makanan Kering di Harris Hotel & Conventions Bundaran Satelit Surabaya - Hajar Alfina Alfadani; Any Sutiadiningsih; Asrul Bahar; Ita Fatkhur Romadhoni (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the process of receiving, storing, and distributing dry food ingredients at Harris Hotel & Conventions Bundaran Satelit Surabaya. The research method used is descriptive qualitative, with data collection techniques using observation, documentation, and interviews conducted with three informants consisting of Chef de Partie, Cassual Raguler from the Pastry section, and cold kitchen. The results of this study indicate that the application of FIFO and FEFO has been applied even though the implementation is less consistent. In addition, the management of Bin Cards, especially in terms of recording and updating data, is less consistent. In conclusion, Harris Hotel & Conventions Bundaran Satelit Surabaya has carried out the operational reception of dry food ingredients quite well, but control is needed in the storage and distribution process of ingredients. in this study has several implications for operations at Harris Hotel & Conventions Bundaran Satelit Surabaya. With supervision of the storage and distribution process of food ingredients, it can ensure the quality of ingredients and more optimal operational efficiency, and in stock management it will help minimize the risk of damage to food ingredients.